Overcoming the barriers of combining early flowering and anthracnose resistance in white lupin (Lupinus albus L.) for the Northern Agricultural Region of Western Australia - Adhikari, K.; Thomas, G.; Diepeveen, Dean; Trethowan, R. (CSIRO Publishing, 2013)
White lupin (Lupinus albus L.) is an important grain legume crop in Australia. The anthracnose incursion in the mid-1990s wiped out the white lupin industry in Western Australia (WA). Since then, incorporation of anthracnose resistance has been a major focus in white lupin breeding. After a series of experiments and targeted breeding in WA, high-yielding anthracnose-resistant genotypes were developed. One of these lines, Amira, was released in 2012 as a replacement for the then-benchmark variety Andromeda. Amira is high-yielding and early-maturing and it has substantially improved resistance to anthracnose compared with Andromeda. Its yield and grain quality are similar to Kiev Mutant and it will be suitable for growing in parts of the Northern Agricultural Region of WA where anthracnose risk is moderate to low. With the adoption of this new variety, reliable production of white lupin can recommence in WA. The growing season in WA is characterised by terminal drought, and early flowering is as important as anthracnose resistance. However, combining these traits was difficult and their combination was not achieved at a desired level in earlier work. The incorporation of the early-flowering trait from a different genetic source from France demonstrated that it is possible to combine these traits at an appropriate level. There was no genetic linkage between the two traits, and consequently, new genotypes with earlier phenology and higher levels of resistance than Amira were developed. The combination of early flowering and anthracnose resistance represents a breakthrough that will significantly improve the adaptation and profitability of white lupin production in WA. © CSIRO 2013.